Reinforcing the impacts of work release on prisoner recidivism: the importance of integrative interventions - Weisburd, David (Journal of experimental criminology, 2017)
We present findings from an evaluation of a large work release program in the Israeli Prison Service. The Israeli program uses an integrative therapeutic approach which combines work release with a series of other program elements. Our main question is whether this integration of multiple program elements leads to strong benefits in terms of reincarceration and re-arrests.